Integrated Aquaculture Networking Workshop - Report To The Indigenous Land Corporation - Evans, Louis; Cronin, Darryl (2006)
OverviewThe Northampton workshop was convened by the Centre for Sustainable Mine Lakes (CSML) and the Central West College of TAFE in association with the Ngalang Boodja Council, Collie. The workshop was conducted at Gregory Springs Farm, Northampton from 16 to 18 November 2005 through funding provided by the Indigenous Land Corporation, the Mid West Development Commission, Central West College of TAFE, Desert Knowledge CRC and the Centre for Sustainable Mine Lakes.The primary goals of the workshop were to:promote an opportunity to start developing a network of aboriginal people, technical experts and farmers involved in integrated aquaculture to identify effective approaches to build capacity of aboriginal people to develop sustainable enterprises on integrated aquaculture;enhance the technical knowledge and understanding of integrated aquaculture by aboriginal participants and create an opportunity for the Collie aboriginal participants to network with other aboriginal people involved in or interested in aquaculture ventures;introduce inland integrated aquaculture to aboriginal people and farmers to aid in the development and implementation of local opportunities for income diversification;start building a database with aboriginal people and farmers inputs regarding their needs and challengers to develop potential aquaculture business;The workshop comprised a two day course in integrated aquaculture, delivered by CSML, Muresk Institute and TAFE staff and Mr Frank Mauger, Gregory Springs Farm, for Aboriginal community members from South West and Mid West Aboriginal communities. The course was followed by a one day open seminar attended by the course participants and tutors, along with farmers from the Mid West region, other Aboriginal people and government agency representatives.Aboriginal participation and industry involvementMembers from four Aboriginal communities attended the two day workshop - Ngalang Boodja Aboriginal Community, Collie (5 people), Barrel Well Aboriginal Community, Kalbarri (5 people), Moonie Mia Aboriginal Community, Northampton(2 people) and the Yarrlgu Bunna Aboriginal Corporation, Yalgoo (4 people). Attendees from the three major groups all included community elders and young people interested in aquaculture. A school teacher from the Pia Wadjarri Remote Community School, located about 200km from Yalgoo, also attended the course as did 6 members of the CSML Mining for Country team, Mr Frank Mauger from Gregory Springs and 4 staff members from the Geraldton College of TAFE.Two representatives from the Tjupan Ngalia Aboriginal Tribal Council had also planned to attend the course but were unable to attend due to family commitments.In addition to the course attendees, a further 9 farmers, 3 more Aboriginal people and representatives from the Mid West Development Commission, the Mid West Business Enterprise Centre and the Geraldton Branch of the WA Department of Environment, attended the one day seminar, giving a total workshop attendance of 44 people.OutcomesThe workshop was an undoubted success. During the first two days of aquaculture training course, the Aboriginal attendees demonstrated enthusiasm and a keen interest to learn more about integrated aquaculture. At the seminar, conducted on the final day, local farmers demonstrated interest in improving their knowledge regarding aquaculture, looking for new opportunities to diversify their income and assess likely returns from investing in this type of business. The CSML and TAFE staff who delivered the course also benefited from their participation.Some of the more noticeable general outcomes for the Aboriginal participants from the workshop were:Interest and enthusiasm to learn more about integrated aquaculture and move towards developing an aquaculture venture;Commitment to a cooperative approach to enterprise development, learning and sharing of knowledge and support of each other;An understanding of the aquaculture industry and an insight into what local farmers are thinking about in regards to the industry;Some of the noticeable outcomes for CSML, Muresk and TAFE staff were;An understanding of the aspirations of Aboriginal people in regards to integrated aquaculture, enterprise development or community development;Greater awareness of the complexities and barriers associated with Aboriginal training, employment creation and enterprise development;A commitment to be involved in another integrated aquaculture workshop with Aboriginal people and future capacity building activities.Learning outcomesThe goal of the two day program was to provide an overview of the various facets of integrated aquaculture, with emphasis on practical demonstrations. The wide range of topics covered precluded any opportunities for students to develop competencies in any particular procedures or techniques. However, there was significant learning with respect to an increase in knowledge and understanding of the principles and practices of integrated aquaculture.During the two day course the Aboriginal participants gained insight into:The basic principles of cultivating fish with emphasis on cultivation systems, feeding approaches and general animal husbandry techniques;The important water quality parameters that affect fish health and how to control these parametersImportant considerations in managing a fish farm operationHow to hatch live feedsApproaches currently being used in marron aquacultureApproaches used in the propagation and cultivation of native plantsInsight was also gained into how to link an aquaculture venture with plant cultivationEvaluationOver the first two days of the workshop, feedback was sought from all of the Aboriginal participants in regards to the course. This was not a formal evaluation, but an exercise to seek Aboriginal views and opinions. Generally they were asked:What they thought of the courseDid they find the information useful?Could they use the information in any way?Could things have been done better?The common themes from the answers to these questions were as follows:The participants felt that the course and the information presented were interesting, stimulating and informative. Generally they understood the information, but would have preferred more hands-on activities or hands-on practical informationAn important issue was how to move from doing a course to establishing an enterprise because community groups lacked the skills and abilities to obtain funds and write submissions. However it was understood that a cooperative approach between all the Aboriginal groups will give them a stake in the industry and provide the forum for sharing information and knowledge.There was also concern that because of the barriers to economic development for Aboriginal communities, they would be disadvantaged and other sectors of society would take the initiative, taking advantage of aquaculture technology and information. Some participants expressed the view that Aboriginal people want a fair go in enterprise development. There was also a view that the talking and well wishing had to be backed up with action.Issues and recommendationsThe following topics of relevance to future networking and enterprise development are addressed in the report:Aboriginal networking and participatory decision making processesEconomic or commercial advantage of an Aboriginal networkNetworking across the divideHands-on learningFormalising the course - objectives and competenciesLinking the scientific with the social, cultural, economic and environmentalProtecting and using Aboriginal knowledgeCSML Curtin University, Central West TAFE and Frank Mauger CollaborationRecommendations to address the issues raised in relation to these various topics are as follows:Recommendation 1: The project should a participatory and consensus building approach to discussion and decision making.Recommendation 2: An Aboriginal Networking Cooperative should be formed to advance enterprise development by Aboriginal peopleRecommendation 3: Further efforts should be made to establish a network of Aboriginal and non-Aboriginal people who have a common interest in integrated aquacultureRecommendation 4: For future short courses there needs to be a greater focus on developing a style and method that incorporates hands-on activities and discussion.Recommendation 5: A review of current courses that incorporate aquaculture, plant cultivation, enterprise development and governance, should be conducted with the aim of creating a short course in integrated aquaculture specifically designed for Aboriginal people.Recommendation 6: Integrated aquaculture training must be contextualized within the social, cultural, economic and environmental aspects of Aboriginal life.Recommendation 7: Initiatives aimed at creating networks to share knowledge between Aboriginal people and the wider society need to respect the right of Aboriginal people to own, control, manage, protect and use their traditional knowledge. The right of Aboriginal people to receive fair and equitable compensation and/or benefits for the use of their knowledge must also be respected.Recommendation 8: CSML and Muresk staff from Curtin University, Central West College of TAFE staff and Frank Mauger should continue to work together to assist facilitate the development of integrated aquaculture ventures with Aboriginal people. Facilitation emphasises advocacy, networking, training, technical support and monitoring.Future actionsThere is commitment from all parties to take this project forward. Three key future activities were identified:1.Strategic planning There needs to be a planning process undertaken in each participating Aboriginal community to identify their aspirations, define their goals and objectives, identify resource needs and identify where funding and resources can be obtained.2.Integrated aquaculture network A network of Aboriginal communities interested in developing integrated aquaculture ventures should be established. Another training and development workshop should be held. The purpose of this workshop and future workshops would be to bring the Aboriginal groups together to share ideas and information, acquire knowledge and skills, identify enterprise or socio-economic project opportunities and to assist the Aboriginal groups develop theses projects.3.Enterprise development projects local Aboriginal community enterprise or socio-economic projects should be identified and funds and other resources sought to assist those communities develop and establish projects.